2016
DOI: 10.1007/s11770-016-0547-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic method for measuring water holdup of low velocity and high-water-cut oil-water two-phase flow

Abstract: Oil reservoirs with low permeability and porosity that are in the middle and late exploitation periods in China's onshore oil fi elds are mostly in the high-water-cut production stage. This stage is associated with severely non-uniform local-velocity flow profiles and dispersed-phase concentration (of oil droplets) in oil-water two-phase flow, which makes it diffi cult to measure water holdup in oil wells. In this study, we use an ultrasonic method based on a transmission-type sensor in oil-water two-phase flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…As for slug flow and churn flow, we will give the specific measurement scheme below. We used the ultrasonic sensor to measure oil-water two-phase flow in a previous work, and the results suggested that the attenuation of ultrasonic pulse is not significant when the diameter of the oil bubble is less than 1 mm [20]. In the oil-gas-water three-phase flow, due to the injection of gas, oil and water have been mixed into an emulsified state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for slug flow and churn flow, we will give the specific measurement scheme below. We used the ultrasonic sensor to measure oil-water two-phase flow in a previous work, and the results suggested that the attenuation of ultrasonic pulse is not significant when the diameter of the oil bubble is less than 1 mm [20]. In the oil-gas-water three-phase flow, due to the injection of gas, oil and water have been mixed into an emulsified state.…”
Section: Resultsmentioning
confidence: 99%
“…Focusing on void fraction measurement in oil-gas-water three-phase flow, because of the heterogeneous distribution of the gas phase. The ultrasonic sensor consisted of single receiver is insufficient to accurately measure void fraction [19,20]. In this paper, a mutually perpendicular ultrasonic sensor (MPUS) system composed of two pairs of ultrasonic transducers positioned opposite to each other was designed to measure the void fraction of heterogeneous flow in oil-gas-water three-phase flow.…”
Section: Introductionmentioning
confidence: 99%
“…The oil-water two-phase flow in the oil well has complex flow regimes with random and variable oil-water interface, as well as a serious slip effect between the oil and water phases. These problems have caused major challenges to traditional production profile logging, such as spinner flowmeter responds poorly under low flow conditions, and the fluid capacitance has poor response under high water cut conditions [2]. Ultrasonic multiphase flow logging tool is a logging method that uses the ultrasonic Doppler effect and the difference in acoustic impedance between oil, gas, and water and uses the spectral characteristics of the discrete phase reflected sound waves to obtain the flow of fluids in each phase [3].…”
Section: Introductionmentioning
confidence: 99%
“…Exemplos de sensores comerciais são os visores ou medidores mecânicos de nível e sensores de pressão ou capacitivos montados internamente ao reservatório, além de sensores radioativos, eletrônicos, térmicos,ópticos e hidráulico. No entanto, um dos métodos que atendem os requisitos restritivos devidoà aplicação na indústria do petróleo utiliza propagação de ondas ultrassônicas empregando sensores montados externamente (Lee et al, 2005;Sakharov et al, 2003;Subhash and Balasubramaniam, 2014;Zhao et al, 2016). A aplicação do ultrassom em reservatórios de armazenamento e vasos de separaçãoóleoagua por segregação gravitacional para caracterização das interfaces entre os diversos fluídos no interior deles e identificação de suas propriedadesé um desafio que não foi totalmente superado pelas tecnologias existentes (Mukherjee et al, 2020;Alshaafi et al, 2020;Leal-Junior et al, 2018) Sensores de ultrassom são largamente utilizados na indústria de processos e as suas diversas técnicas atualmente empregadas em monitoramento fazem dessa uma aplicação promissora (Hauptmann et al, 2001).…”
Section: Introductionunclassified